2013
DOI: 10.1155/2013/598325
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Neuroendocrine Carcinoma of the Urinary Tract Successfully Managed with Neoadjuvant Chemotherapy

Abstract: Introduction. Small cell neuroendocrine carcinomas of the urinary tract is an extremely rare entity and very few cases have been reported in the literature. Small cell neuroendocrine carcinoma of the urinary tract (SCC-UT) is the association between bladder and urinary upper tract-small cell carcinoma (UUT-SCC). It characterized by an aggressive clinical course. The prognosis is poor due to local or distant metastases, and usually the muscle of the bladder is invaded. Case Presentation. We report a rare case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“… 30 Our data have confirmed that the incidence of ureteral SCC is highest in Asian countries, which may be attributed to genetic susceptibility, dietary habits or environmental factors. 22 Consistent with previous reports, 21 the most commonly presenting symptoms were gross hematuria and flank pain. To date, no patient presented with paraneoplastic syndrome due to inappropriate hormone secretion.…”
Section: Discussionsupporting
confidence: 88%
“… 30 Our data have confirmed that the incidence of ureteral SCC is highest in Asian countries, which may be attributed to genetic susceptibility, dietary habits or environmental factors. 22 Consistent with previous reports, 21 the most commonly presenting symptoms were gross hematuria and flank pain. To date, no patient presented with paraneoplastic syndrome due to inappropriate hormone secretion.…”
Section: Discussionsupporting
confidence: 88%
“…These case reports utilizing Cisplatin-based neoadjuvant chemotherapy followed by surgery have reported disease-free survival times of 24 to 38 months, 13,14 whereas a prior study of 39 patients with small cell carcinoma of the upper urinary tract reported an overall survival time of only 15 months in patients managed with surgery alone or surgery with adjuvant chemotherapy. 5 Although validation in larger cohorts is needed, taken together these findings suggest that early institution of chemotherapy may be pivotal in improving survival in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…For treatment, most scholars suggest combining radical bladder dissection and chemotherapy to improve clinical effectiveness. Of course, there are also some scholars adopting neoadjuvant chemotherapy, which has been shown to have good efficacy (4). In recent years, the development of molecular targeted therapy for malignant tumors has advanced and some investigators suggest that molecular targeted therapy of BNEC using epidermal growth factor receptor (EGFR), B-cell lymphoma 2 (Bcl-2) and CD56 might hold promise, potentially bringing significant improvement to the survival rate of BNEC patients (17).…”
Section: Discussionmentioning
confidence: 99%